1973
DOI: 10.1346/ccmn.1973.0210503
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Oxidation of Benzidine and Aniline by Montmorillonite and Hectorite

Abstract: Abstract--Quantitative measurements are made of the adsorption of benzidine and aniline from aqueous hydrochloride solutions by Na-, Li-, and Ca-montmorillonite and of the displaced inorganic cations. From these data, the ionic states of the adsorbed organic species are determined. Under conditions of controlled pH, the adsorption of benzidine increases as the pH increases, and involves mainly divalent species at pH < 3.2, and increasing proportions of monovalent and neutral species at pH > 3.2. With aniline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 11 publications
(18 reference statements)
1
34
0
Order By: Relevance
“…Thus, the clay appeared to be necessary to stabilize the blue semiquinone product, playing a more specific role than that of a simple oxidizing agent. This has previously been indicated by the fact that H202 alone could not form benzidine-blue, but H202 plus hectorite could (Furukawa and Brindley, 1973).…”
Section: Mechanism Of Benzidine-blue Reaction On the Claymentioning
confidence: 77%
“…Thus, the clay appeared to be necessary to stabilize the blue semiquinone product, playing a more specific role than that of a simple oxidizing agent. This has previously been indicated by the fact that H202 alone could not form benzidine-blue, but H202 plus hectorite could (Furukawa and Brindley, 1973).…”
Section: Mechanism Of Benzidine-blue Reaction On the Claymentioning
confidence: 77%
“…The surface charge densities in montmorillonite and in vermiculite can cause different packing arrangements in their benzidine intercalates. There is room for both divalent (Furukawa and Brindley, 1973) and monovalent benzidine cations to lie flat and to satisfy the exchange capacity of montmorillonite. In vermiculite, only divalent cations would have sufficient room to lie flat; monovalent species would have to stand at an angle to the surface and so give rise to spacings above 15.5/~, in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…By quantitatively studying the adsorption of benzidine from aqueous hydrochloride solutions in contact with various montmorillonites, Furukawa and Brindley (1973) concluded that at pH <3.2, divalent and monovalent species were taken up by displacement of the exchangeable cations, but at higher pH, the monovalent species was preferentially adsorbed. They further considered that the total amount of benzidine adsorbed was equal to the amount of unoxidized cation taken up by exchange plus an amount of semiquinone produced by oxidation-reduction processes.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of this yellow complex has been explained variously, such as a protonated monoradical cation, or a diimine or quinoidal cation. The following disproportionation mechanism to produce the yellow complex is supported from various experimental evidences (45)(46)(47):…”
Section: Reactions Due To Lewis Aciditymentioning
confidence: 88%